Religionswissenschaft, quo vadis? - Ulrike Kollodzeiski (Zeitschrift für Junge Religionswissenschaft)
This article depicts the development of the scientific study of religion in Germany within the last ten years on the basis of professorships and ventures a prognosis for the next ten years. In 2010, ensuing from a so-called return of religion and the subsequent high social relevance of the discipline, the Wissenschaftsrat (academic council) advocated reinforcing the study of religion through more professorships. This recommendation has been pursued throughout many places. However, the growth of professorships does not correspond to an equally increased presence of the study of religion in non-academic discourses. Here, other disciplines such as the theologies, history, and sociology are more likely to be heard. Given the downward trend of student numbers as well as the closures of other small disciplines, the urgent question arises as to how the study of religion should position itself strategically as a discipline and how it shall fulfill its social relevance in the future.